Efektifitas Promosi Bank Sulselbar Melalui Film Aman Bos - yasa, Miyarta; Satria, Christofer; Arfa, Muhammad (Universitas Bumigora, 2022)
This study describes the effectiveness of promotion through the film Aman Bos, a film that is shown in cinemas and YouTube. The aim is to promote Bank Sulselbar, the methodology by conducting case studies and literature studies to review this case. Using the scalpel of Kotler's theory with the 4 product mix marketing approach, price, promotion and place. The research results show that through the media YouTube for promotion is very effective in expanding audience reach, this promotional media is quite effective as a medium to attract consumers, as a conclusion from research describing the level of effectiveness of films for very effective promotional media.